The presidents and the pastime : the history of baseball and the White House - Smith, Curt (University of Nebraska Press, 2018)
"The Presidents and the Pastime draws on Curt Smith's extensive background as a former White House presidential speechwriter to chronicle the historic relationship between baseball, the "most American" sport, and the U.S. presidency. Smith, who USA Today calls "America's voice of authority on baseball broadcasting," starts before America's birth, when would-be presidents played baseball antecedents. He charts how baseball cemented its reputation as America's pastime in the nineteenth century, such presidents as Lincoln and Johnson playing town ball or giving employees time off to watch. Smith tracks every U.S. president from Theodore Roosevelt to Donald Trump, each chapter filled with anecdotes: Wilson buoyed by baseball after suffering disability; a heroic FDR saving baseball in World War II; Carter, taught the game by his mother, Lillian; Reagan, airing baseball on radio that he never saw--by "re-creation." George H.W. Bush, for whom Smith wrote, explains, "Baseball has everything." Smith, having interviewed a majority of presidents since Richard Nixon, shares personal stories on each. Throughout, The Presidents and the Pastime provides a riveting narrative of how America's leaders have treated baseball. From Taft as the first president to throw the "first pitch" on opening day in 1910 to Obama's "Go Sox!" scrawled in the guest register at the National Baseball Hall of Fame in 2014, our presidents have deemed it the quintessentially American sport, enriching both their office and the nation."--